2004
DOI: 10.1638/04-005
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Sex Determination and Gonadal Manipulation in Gulf of Mexico Sturgeon (Acipenser Oxyrinchus Desotoi)

Abstract: Seventeen Gulf of Mexico sturgeons (Acipenser oxyrinchus desotoi) underwent endoscopic sex determination, gonadal biopsy, and various reproductive surgeries as part of a conservation development plan. The fish were anesthetized with tricaine methanesulfonate (MS-222) buffered with sodium bicarbonate and maintained on a recirculating water anesthesia circuit. A 6-mm Ternamian EndoTip Cannula, placed through the ventral midline, midway between pectoral and pelvic fins, permitted the introduction of a 5-mm telesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 15 publications
2
22
0
1
Order By: Relevance
“…The incisions made for the trocater introduction did not cause external bleeding and no any apparent damage to the internal organs was found by image inspection. Similar results were observed by Hernandez-Divers et al (2004) for sturgeon, Acipenser gueldenstaedtii. Froehlich et al (1999) suggested that there is always a risk in any surgical procedure, but the risk is generally low with laparoscopy, as shown in sturgeons.…”
Section: Laparoscopic Proceduressupporting
confidence: 87%
“…The incisions made for the trocater introduction did not cause external bleeding and no any apparent damage to the internal organs was found by image inspection. Similar results were observed by Hernandez-Divers et al (2004) for sturgeon, Acipenser gueldenstaedtii. Froehlich et al (1999) suggested that there is always a risk in any surgical procedure, but the risk is generally low with laparoscopy, as shown in sturgeons.…”
Section: Laparoscopic Proceduressupporting
confidence: 87%
“…Less‐invasive alternatives to coeliotomy for sex determination in sturgeon include analysis of blood hormone levels (Webb et al., 2002; Feist et al., 2004; Viayeh et al., 2006), ultrasonography (Moghim et al., 2002; Colombo et al., 2004; Wildhaber et al., 2005; Bryan et al., 2007) and endoscopy (Kynard and Keiffer, 2002; Hernandez‐Divers et al., 2004; Wildhaber et al., 2005; Bryan et al., 2007; Hurvitz et al., 2007; Divers et al., 2009). Blood hormone analysis requires specialized laboratory equipment and expertise, results are not immediate and confirmation of this approach has not been tested on Atlantic or shortnose sturgeon.…”
Section: Introductionmentioning
confidence: 99%
“…Coeliotomy is an invasive technique but does not require the use of sophisticated devices (Filho et al, ). The major problems in the application of this technique are post‐operative complications, including haemorrhage, wound dehiscence, contamination and infection (Boone, Hernandez‐Divers, Radlinsky, Latimer, & Shelton, ; Hernandez‐Divers et al, ). According to Filho et al (), the accuracy degree using this technique reached 96.3% for males and 93.9% for females of Lophiosilurus alexandri .…”
Section: Resultsmentioning
confidence: 99%